Institutional Weakness and National Security in Developing Nations - Zaheer, Izba; Gul, Sabaina (ACADEMIA International Journal for Social Sciences, 2026)
One of the most impactful but analytically unspecified variables in the comparative study of national security is institutional weakness. This article constructs a systemic model of the manner in which the absence of governance in developing federal states is converted into actual security weaknesses. Based on comparative case study in Nigeria, Pakistan, Ethiopia, Brazil, and the Democratic Republic of Congo, we are able to identify four main mechanisms of institutional instability to breakdown of security which include: hallow of legitimate use of monopoly of force by the state, fragmentation of inter-governmental coordination, expansion of ungoverned spaces where non-state armed actors could operate and delegitimization of the state by the peripheral populations. We state that federalism, which aims at diversity management and decentralization of power, may under weak central institutions conditions, backfire and increase these channels, as well as by diffusing responsibility and establishing jurisdictional cracks. The article represents a diagnostic taxonomy of institutional feebleness and security associates, and offers an analysis plan on comprehending when and how federal framework can be restructured to strengthen as opposed to disintegrate state security capacity.